1999
DOI: 10.3397/1.599303
|View full text |Cite
|
Sign up to set email alerts
|

Physiological cost of energy-equivalent exposures to white noise, industrial noise, heavy metal music, and classical music

Abstract: The results of a study comparing hearing-physiological effects of four energetically equivalent, but different, sound exposures are reported. All exposures were for a period of 1 h at a mean A-weighted sound pressure level of 94 dB. The four sound exposure sources were white noise, industrial noise "primarily metal working…, a medley of typical heavy metal music, and a selection of classical music. Threshold shifts and restitution time were measured for all exposures. The results of this study suggest that hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The results for European classical music in this study almost exactly match the results of Strasser et al (1999), Strasser et al (2003) and . The same classical music exposure had led to audiometric characteristic values of strain that were almost identical to those found in this study.…”
Section: Results In the Light Of Other Comparable Studiessupporting
confidence: 94%
See 1 more Smart Citation
“…The results for European classical music in this study almost exactly match the results of Strasser et al (1999), Strasser et al (2003) and . The same classical music exposure had led to audiometric characteristic values of strain that were almost identical to those found in this study.…”
Section: Results In the Light Of Other Comparable Studiessupporting
confidence: 94%
“…The former consisted of string instrument passages instead of compositions for wind instruments. Additionally, Strasser et al (1999) also used classical music and heavy metal music as test exposures to make a comparison to industrial noise and energy-equivalent 'white noise'. Both studies' results were consistent with the findings of this study.…”
Section: Results In the Light Of Other Comparable Studiesmentioning
confidence: 99%
“…80 dB(A)). However, Strasser et al (1999) found TTS in subjects exposed for 1 h to noise or music with a level of 94 dB(A), respectively. Engdahl (1996) found both a shift in pure-tone threshold and DPOAE level in subjects exposed for 10 min to third octave band noise around 2 kHz with 102 dB SPL.…”
Section: Factory Workers Exhibited Small Changes In Pure-tone Threshomentioning
confidence: 93%
“…Regarding the effects of alcohol and cigarette smoke exposure, they must be considered "initial findings" from "feasibility studies." In comparison with previous audiometric studies (cp., e.g., Irle, Hesse, & Strasser, 1998;Strasser, Hesse, & Irle, 1995;Strasser, Irle, & Scholz, 1999), the results in this study are less pronounced and exhibit less distinct differences with respect to the effects of test parameters.…”
Section: Discussionmentioning
confidence: 57%